Bronchopulmonary dysplasia: an old and new disease - Caterina Franco; Flavia Petrillo; Antonio Del Vecchio (Hygeia Press di Corridori Marinella, 2014)
Bronchopulmonary dysplasia (BPD) is one of the most common and significant medical complications associated with prematurity. It is made more serious by its morbidity and mortality rates. Although recent advances in clinical practice (prenatal steroids, surfactants, new ventilatory strategies, nutritional support) have contributed to improving the clinical course and outcomes of neonates with BPD, its overall incidence has not changed in the last decade owing to a concomitant increase in survival of prematures. The incidence of BPD is in fact inversely proportional to birth weight: 30% for neonates weighing less than 1,000 g, with different percentages in the single centres depending on clinical management and the ventilation criteria applied. However, to date, BPD represents not only a chronic pulmonary pathology in infancy that prevalently affects premature neonates who undergo mechanical ventilation and oxygen therapy for respiratory distress syndrome (RDS), but also prematures with minor signs of initial pulmonary pathology or term neonates requiring aggressive ventilatory support due to an acute and severe lung pathology. Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken